The Role of Employee Knowledge, Providers, Environment, and Processes in Service Differentiation Strategy: A Study on a Sample of Service Institutions in Baghdad - Hameed Shukur Abdul Ameer Al-Azzawi; Aymen Hadi Talib; Basim K. M. Nasrawi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Organizations have faced numerous challenges in their pursuit of expanding creativity due to the current market realities, necessitating the adoption of new mechanisms to address competition in contemporary markets. Knowledge is considered a key element in enhancing an organization's ability to succeed and excel, particularly through differentiation and sustaining competitive advantages. This research focuses on examining the role of knowledge in service differentiation strategies in service organizations in Baghdad. The study identifies the knowledge requirements and their impact on building these strategies. The research employed a descriptive-analytical approach, distributing a questionnaire to 115 managers in various service organizations in Baghdad, with 104 valid responses being retrieved for analysis using the SPSS software. The results revealed a significant correlation and impact between marketing knowledge and its various dimensions (such as employees, environment, suppliers, and processes) and the service differentiation strategy. The results revealed a significant impact of knowledge on the service differentiation strategy in the studied institutions. It was found that knowledge explains 42.1% of the variation in the differentiation strategy, with each increase in knowledge leading to an increase in differentiation. Additionally, the results highlighted a significant impact of knowledge in various areas, such as employee knowledge (which explains 26% of the variation), environmental knowledge (which explains 23.3%), provider knowledge (which explains 16%), and process knowledge (which explains 31.3%). These factors collectively demonstrated that increasing knowledge in each area contributes to the enhancement of the service differentiation strategy, thus confirming the hypothesis of the study that a significant relationship exists between knowledge and differentiation strategy.